Comparative analysis of innovative cooling systems for Li-ion cells using carbon-graphene coatings, metal foams, and 3D printing - Luigi Sequino; Bianca Maria Vaglieco (Case Studies in Thermal Engineering)
The amount of energy required has increased abruptly in recent years. The road toward clean cities and transportation has pushed the utilization of electric cars and the supply of energy storage systems. However, electric vehicles operate at high working temperatures, so designers must devote considerable effort to developing efficient cooling systems. The complexity of battery-cooling solutions varies with the application: city cars, trucks, and hyper-cars require increasingly sophisticated systems. Furthermore, advanced unconventional materials often provide the most effective way to build components tailored to a specific application. This work presents different configurations of cooling systems for lithium-ion cells. One consists of graphene-carbon coatings for heat dissipation via natural convection with air. In the second, a metal foam-based frame has the double aim to support and cool down the battery pack, both in natural convection and with a local cold point. Finally, the third example consists of a 3D-printed channel plate, with a custom-built design, where water is used for the liquid cooling. Each solution is experimentally investigated, monitoring the electric signals and using contact and contactless methods for temperature detection. A comparison between the three configurations has been performed in terms of the cell increment of temperature versus cell internal heat generation. The reported results provide a guide for the selection of the optimal cooling system oriented to the application.